The Violation of Maxims and The Conversational Implicature in ‘Hichki 2018’ Movie - Hendra Efendi; I Made Suta Paramarta; Risman Iye (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
In a movie, the characters often violate maxims and conversational Implicatures to boost a dramatic impression of the movie. This research was conducted to analyze the violation of maxims, in which the violations found can cause conversational implicature. The research is a qualitative study. The research subject is an inspirational Bollywood film entitled